Transformation of Hadji Kalla's Thought and Policy in Managing Kalla Group's Business from a Amanah Perspective - Kasim, Sjaiful; Kara, Muslimin H; Abdullah, Muhammad Wahyuddin; Murtiadi, Murtiadi (Universitas Muhammadiyah Sorong, 2024)
This research aims to: 1) description of Hadji Kalla in managing business 2) The foundation of Hadji Kalla's thinking in running the business 3) Business management done by Hadji Kalla in the perspective of Amanah metaphor and 4) Model of thought transformation in Kalla Group company. Qualitative research using grounded theory phenomenalogical approach informants consist of Directors of Holding Company and two retired employees who had interacted with Hadji Kalla in his time. The results of the study; (1) Hadji Kalla as an entrepreneur started as a child and continued his business to Watampone, Bone and Makassar. In Makassar established the company NV HADJI KALLA (1952) engaged in import and export, the first importer of Japanese cars TOYOTA brand, (2) In running his business always juxtapose it with religion so that all business activities, social society, Hadji Kalla view work is worship. (3) In business management, Kalla Group has formulated corporate value into the foundation of policy in the form of five Kalla Value (4) The transformation of Hadji Kalla's thinking that took place from the first generation (Hadji Kalla) to the second generation (JK and FK) to the third generation (SJK) through the method of mentoring by experience. The transformation process of Hadji Kalla's thinking regarding Work is Worship, underwent development, addition and emphasis on aspects of work quality improvement, sincerity, BMW (Cost Quality Time) method, Faith Work Ethic, Performance, and changes in business orientation to a portfolio based on usefulness (maslahah), synergy and balance. The Kalla Value that has been applied becomes a distinctive feature that shapes the entrepreneurial spirit. Researchers call this the KALLAPRENEUR phenomenon, which is a trustworthy entrepreneurial posture, full of Islamic spirituality values using modern managerial approaches and local wisdom.